Penguatan Pendidikan Karakter dalam Implementasi Kurikulum Merdeka: Kajian Literatur - Ria Agustina; Agustina Agustina; Novia Juita; Edo Yuliandra Pratama (Journal on Education, 2024)
The purpose of this research is to examine the strengthening of character education in the implementation of the independent curriculum. With the Systematic Literature Review approach, it can provide information on whether schools have understood the independent curriculum, what are the obstacles faced by schools, and whether the Pancasila student profile has been implemented so that it becomes the character education of the whole student. This study examines 5 articles on strengthening character education in the implementation of the independent curriculum. From the results of the SRL, it can be concluded that strengthening character education in the implementation of the independent curriculum has obstacles, among others, not fully understanding the essence of "independent learning" so that it has not been able to optimize the strengthening of the Pancasila learner profile, limited time informed by the learners, limited time in learning activities, little subject substance, limited technological knowledge owned by the learners, very less learner attention to subjects and so on. According to the findings of this research, the independent curriculum is most effective in developing the character of its students through the development of the Pancasila student profile. Pancasila students engage in project-based learning activities as part of their profile development. The Pancasila learner profile is expected to produce graduates who demonstrate the characteristics and abilities or skills that are needed and achievable, as well as possessing the necessary skills and knowledge.